2010
DOI: 10.4062/biomolther.2010.18.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Plasma Testosterone/LH Ratio in Male Mice Exposed to Sodium Arsenite

Abstract: -While it's been shown that arsenic impairs male reproductive function, it remains unclear whether the mechanism involves an effect on testosterone (T) production. We examined plasma T and luteinizing hormone (LH) levels in mice given water containing either 20 or 40 mg/L sodium arsenite (SA). The plasma T levels were lower in SA-treated mice than in controls and correlated well with testicular T levels within individuals. However, SA treatment did not significantly affect plasma LH levels. The ratio of plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several in vivo studies have, however, reported reproductive toxicity in male mice upon exposure to arsenic. For instance, NaAsO 2 induces oxidative stress and adversely affects sperm functions (Monika et al, 2013), reduces steroidogenesis (Chang et al, 2010), and generates spermatotoxic effects (Pant et al, 2004). It is very well established that an imbalance between ROS levels and antioxidant enzymes indicates oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo studies have, however, reported reproductive toxicity in male mice upon exposure to arsenic. For instance, NaAsO 2 induces oxidative stress and adversely affects sperm functions (Monika et al, 2013), reduces steroidogenesis (Chang et al, 2010), and generates spermatotoxic effects (Pant et al, 2004). It is very well established that an imbalance between ROS levels and antioxidant enzymes indicates oxidative stress.…”
Section: Discussionmentioning
confidence: 99%